Effects of Screw Configuration, Screw Speed, and Stearic Acid Addition on the Functional Properties and Structural Characteristics of Maize Starch Extrudates. (8th January 2019) - Panyoo, A. Emmanuel; Emmambux, Mohammad Naushad
Abstract : Starch modification is usually achieved with synthetic chemicals but cannot be referred to as "clean label." Fatty acids, such as stearic acid, can be used to modify starch by forming amylose–lipid complexes (ALCs) to potentially produce non‐gelling "clean label" starches. The objective of this study is to determine the effects of screw configuration, screw speed, and stearic acid addition during extrusion cooking on the properties of extruded maize starch. A 2 × 2 × 3 factorial design is used. That is, two screw types (normal‐ and reactor‐type), two screw speeds (100 and 125 rpm), and three levels of stearic acid (0%, 1.5%, and 4%) are applied at a feed rate of 5 kg h −1 and a barrel moisture content of 40%. The extrudates are dried and milled, and their functional properties, including the water absorption index (WAI), water solubility fraction (WSF), pasting properties, and gel texture, are determined. Extrusion cooking of maize starch with a normal screw and stearic acid (1.5% or 4%) significantly ( P < 0.05) decrease the WAI and first peak viscosity of the maize starch extrudate. Extrusion cooking of maize starch with a normal screw or reactor screw and stearic acid (1.5% or 4%) significantly ( P < 0.05) decrease the gel texture of the maize starch extrudate. Extrusion cooking of maize starch with a reactor screw, stearic acid (1.5% or 4%) and a screw speed of 125 rpm after 90 min of pasting produce more amylose–lipid complexes. Extrusion cooking of maize starch with added stearic acid has the potential to produce non‐gelling "clean label" ALCs. Abstract : Stearic acid can be used to modify starch by forming amylose–lipid complexes to produce non‐gelling "clean label" starches during extrusion cooking. The non‐gelling behavior during pasting observed for the starch extrudate with added stearic acid could be due to the formation amylose–lipid complexes. Thus extruded starch can be used to produce amylose–lipid complexes. Amylose–lipid complexes produced by extrusion cooking maize starch with stearic acid has the potential to be used as a non‐gelling "clean label" starch.